Locally based syncretic literacy practices among multicultural students in North Sumatra - Jubilezer Sihite; Rotua Elfrida Pangaribuan; Nenni Triana Sinaga (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2026)
This study reveals how different multicultural students in North Sumatra interpret heritage symbols as literacy artifacts available in their new place, and how the assimilation process occurs in the context of broader literacy practices in the surrounding environment. Through a participatory case study approach, students were encouraged to capture photographs of literacy artifacts of their choosing within their own environments and to engage in group discussions about these images. The data were analyzed using a framework of syncretic literacy practices, emphasizing acceptance, adaptation, adoption, and synergy or reaction. This study explores ethical meaning-making across different spaces, languages, and modes, examining how multicultural students interpret local culture from their home contexts and whether these interpretations mirror broader faith-based literacy practices within their communities. The results suggest that syncretic literacy practices hold significant potential to inform policy development, enhance the role of literacy in everyday life, and improve literacy education curricula. Moreover, such practices promote the blending and integration of culturally diverse traditions in both the form and organization of literacy activities.